-10(x-1)=-10x+10

Simple and best practice solution for -10(x-1)=-10x+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10(x-1)=-10x+10 equation:


Simplifying
-10(x + -1) = -10x + 10

Reorder the terms:
-10(-1 + x) = -10x + 10
(-1 * -10 + x * -10) = -10x + 10
(10 + -10x) = -10x + 10

Reorder the terms:
10 + -10x = 10 + -10x

Add '-10' to each side of the equation.
10 + -10 + -10x = 10 + -10 + -10x

Combine like terms: 10 + -10 = 0
0 + -10x = 10 + -10 + -10x
-10x = 10 + -10 + -10x

Combine like terms: 10 + -10 = 0
-10x = 0 + -10x
-10x = -10x

Add '10x' to each side of the equation.
-10x + 10x = -10x + 10x

Combine like terms: -10x + 10x = 0
0 = -10x + 10x

Combine like terms: -10x + 10x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| x^2+y^2+8x+22y+37=0 | | x^2+6x-47=0 | | 1.50+1.50m=21 | | 3x+3+4y=7 | | 32=3x+2 | | 22x-10= | | 4x+10y=36 | | 4^5/4^2 | | 6z-6+4z=2 | | h(X)=0.025x^2+1.46x+3 | | 5(y+11)= | | 5w+3=18 | | (6x+5)(13x-15)= | | 35=2x+1 | | -4/3-1/2=2(1/6x-4) | | 60=5y-10 | | 3(5n+6)=10n-2 | | 8y^2(10-6y^3)= | | 105+x+84=180 | | 1/3y×(x-y)= | | 14y+3y-6=4 | | 4(3n-1.2)-0.5=95n+6.2 | | 24x-15=-11 | | f(x)=2x^2-20x-3 | | 3(1+4b)=7b+33 | | 62=4v+10 | | 4v(2)= | | 2q-14=16 | | x^5-2x^4-3x^3+8x^2-4x=0 | | 3x^2+-15x+18=0 | | x/4-7=-11 | | 5y-15=65 |

Equations solver categories